(untitled) (BIRDEM Medical Journal, 2021)
Opportunistic infections, especially invasive fungal infections have emerged as an added health issue in this COVID-era. The dysregulated immune mechanisms in the pathophysiology of COVID-19, its treatment with corticosteroids and other immunomodulatory agents, invasive mechanical ventilation and other forms of ventilatory and oxygen delivery systems, prolonged hospital stay, injudicious use of antimicrobials – all have set the required stages for such infections. Aspergillus spp. and Mucorales are ubiquitous, environmental fungus; may colonize in airways and chronically damaged human lungs, without significant health effects and cause disease, especially in immunocompromized patients. We report case history of a middle aged Bangladeshi man with multiple comorbidities, who presented with fever and respiratory symptoms, four-months after recovery from COVID-19. He had Aspergillus and Mucors on sputum microscopy and cultures; but his response to antibiotics suggested these were colonozations in previously injured lungs by tuberculosis in the form of fibrosis and bronchiectasis. He is well and free of symptoms, two-months since discharge. BIRDEM Med J 2021; 11(3): 218-222